Transformation of social and ecological systems - Emilio F. Moran (Política & Sociedade)
The evolution of social ecological systems is characterized by a lengthy process of steady of slow population growth, appropriation of natural resources, and ever growing complexity. From hunter gatherers first, to extensive and then intensive farmers, to urban industrial aggregations has taken place worldwide in episodic and highly differentiated geographical distribution. It is in the last 50 years that this process has begun to go exponential and to have planetary significance. What used to be episodic periods of regional growth and expansion in the use of resources has grown into a cumulative process that now threatens the planet through the emission of global warming gases, climatic change, and the loss of cultural and biological diversity. The paper identifies some of the changes needed to begin to address this conundrum.